2004
DOI: 10.7589/0090-3558-40.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Time of Oral Rabies Vaccine Baits Relative to Baiting Density and Raccoon Population Density

Abstract: Oral rabies vaccination (ORV) baiting programs for control of raccoon (Procyorl lotor) rabies in the USA have been conducted or are in progress in eight states east of the Mississippi River. However, data specific to the relationship between raccoon population density and the minimum density of baits necessary to significantly elevate rabies im~nunity are few. We used the 22-km2 US National Aeror~autics and Space Administration Plum Brook Station (PBS) in Erie County, Ohio, USA, to evaluate the period of expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 22 publications
0
38
2
Order By: Relevance
“…The overall contact rate with vaccine baits after 7 days in this study was lower than what has been found in similar studies in the United States with the V-RG or alternative baits (Hadidian et al, 1989;Hable et al, 1992;Hanlon et al, 1998;Blackwell et al, 2004). This discrepancy may be explained by differences among study areas in density of raccoons and potentially other species attracted to the bait, as well as the time when these studies were conducted.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…The overall contact rate with vaccine baits after 7 days in this study was lower than what has been found in similar studies in the United States with the V-RG or alternative baits (Hadidian et al, 1989;Hable et al, 1992;Hanlon et al, 1998;Blackwell et al, 2004). This discrepancy may be explained by differences among study areas in density of raccoons and potentially other species attracted to the bait, as well as the time when these studies were conducted.…”
Section: Discussioncontrasting
confidence: 54%
“…This discrepancy may be explained by differences among study areas in density of raccoons and potentially other species attracted to the bait, as well as the time when these studies were conducted. For instance, Blackwell et al (2004) estimated a mean density of 24.5 raccoons/km 2 in their study area, whereas the density near our study site has been estimated at 13 raccoons/km 2 (Monté ré gie, Qué bec, Canada; Jolicoeur et al, 2009). Differences in animal density can, therefore, partly account for the higher rate of disappearance of the V-RG baits in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most commonly for oral wildlife vaccines, the vaccine itself is delivered inside a separate bait, as is the case with existing rabies and classical swine fever wildlife vaccines (Kaden et al, 2003;Blackwell et al, 2004), as well as prototypical vaccines for plague (Creekmore et al, 2002). In the present study we have evaluated the novel FIGURE 3.…”
Section: Discussionmentioning
confidence: 99%
“…When applied at a density of 35 baits/ha, 85% of recaptured possums had indications of bait uptake; this figure was increased to 100% uptake by doubling the baiting density. Both of these baiting densities are markedly higher than those used in wildlife vaccine delivery programs for either mesocarnivores or porcines (Rosatte and Lawson, 2001;Blackwell et al, 2004;Campbell et al, 2006); however, it must be appreciated that possums reach much higher population densities in New Zealand bush because of their utilization of a tree canopy habitat and their monopolization of the browsing niche, thus requiring a higher baiting density. There are estimated to be over 70 million possums in New Zealand, with population densities over 2,000 animals per km 2 reported in favorable broadleaf forest habitats (Efford, 2000).…”
Section: Discussionmentioning
confidence: 99%